(3JgPjH GdcdGe aj JMQjQ GdefWb hGdcdGe GdbSe GdChds - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdJaJGRGfj GdMeO ddg GdPj gOGfG ShGA GdWQjb hHYO agPG ZGjI JgPjH GdcdGe GdbSe GdChd aj GdefWb , ebOeI GdYde Ef cGf EPGYfG ddfSHI aJUOjb hEdG aJUhQs
(3BNQgG (B:s
(3hGdHQgGf Cj GdWQjb Edi Gdhbha Ydi GdMb hGdYed Hg hgPG HGdebGUO CTHg , Je GdbSe GdChd ef GdJgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 219s
(3eYLe GdeDdajf (B3 / 849s
(3cTa GdXfhf (B1/515s
(3TPQGJ GdPgH (B6 / 319s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs